Factors Associated with Household Waste Disposal Behavior among Housewives in Sumber Marga Telang Subdistrict, Banyuasin Regency, in 2025 - Novianti, Leni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Household waste management remain a serious environmental health issue in Marga Telang subdistrict Banyuasin Regency. The behavior of housewives in disposing of waste in influenced by several factors such as knowledge, attitude and availability of waste disposal facilities objective.: to identify the factors influencing houswives behavior in waste disposal in Marga Telang Subdistrict, Banyuasin Regency in 2025. This study used a cross Sectional survey design with 92 randomly selected respondents. Data were collected using a structured questionnaire and analyzed uni Variately and bivariately using the chi square test Results: The analysis showed a significant relationship between knowledge (P =0,014 ) and attitude ( p=0,020 ) with housewives’ waste disposal behavior, and the availability of facilities significantly related( p= 0,001).